Comparative Genomics of Two Sequential Candida glabrata Clinical Isolates. Issue 8 (1st August 2017) - Vale-Silva, Luis; Beaudoing, Emmanuel; Tran, Van Du T; Sanglard, Dominique
Abstract: Candida glabrata is an important fungal pathogen which develops rapid antifungal resistance in treated patients. It is known that azole treatments lead to antifungal resistance in this fungal species and that multidrug efflux transporters are involved in this process. Specific mutations in the transcriptional regulator PDR1 result in upregulation of the transporters. In addition, we showed that the PDR1 mutations can contribute to enhance virulence in animal models. In this study, we were interested to compare genomes of two specific C. glabrata -related isolates, one of which was azole susceptible (DSY562) while the other was azole resistant (DSY565). DSY565 contained a PDR1 mutation (L280F) and was isolated after a time-lapse of 50 d of azole therapy. We expected that genome comparisons between both isolates could reveal additional mutations reflecting host adaptation or even additional resistance mechanisms. The PacBio technology used here yielded 14 major contigs (sizes 0.18–1.6 Mb) and mitochondrial genomes from both DSY562 and DSY565 isolates that were highly similar to each other. Comparisons of the clinical genomes with the published CBS138 genome indicated important genome rearrangements, but not between the clinical strains. Among the unique features, several retrotransposons were identified in the genomes of the investigated clinical isolates. DSY562 and DSY565 each contained a large set of adhesin-like genes (101 and 107, respectively), which exceed by far the number of reported adhesins (63) in the CBS138 genome. Comparison between DSY562 and DSY565 yielded 17 nonsynonymous SNPs (among which the was the expected PDR1 mutation) as well as small size indels in coding regions (11) but mainly in adhesin-like genes. The genomes contained a DNA mismatch repair allele of MSH2 known to be involved in the so-called hyper-mutator phenotype of this yeast species and the number of accumulated mutations between both clinical isolates is consistent with the presence of a MSH2 defect. In conclusion, this study is the first to compare genomes of C. glabrata sequential clinical isolates using the PacBio technology as an approach. The genomes of these isolates taken in the same patient at two different time points exhibited limited variations, even if submitted to the host pressure.